GAMBARAN KUALITAS HIDUP PENDERITA DIABETES MELITUSPADA ANGGOTA DAN NON ANGGOTA KOMUNITAS DIABETES DI PUSKESMAS NGRAMBE - Dika Ernianti; Martini Martini; Ari Udiyono; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Diabetes Mellitus is a chronic metabolic disorder caused by increased levels of blood sugar due to the pancreas is not enough to produce insulin. Diabetes can be suffered for life, needs an evaluation to severity, burden of illness and  management of DM by looking at the quality of life in patients with Diabetes Mellitus. The purpose of this research to describe the quality of life the patients with Diabetes Mellitus on Members and Non Members of Diabetes Community. This research is a descriptive research with cross sectional research approach. The instruments used were DQOL  questionnaires (Diabetes Quality of Life) to measure quality of life, SDSCA (summary of diabetes self care activities) for self-care, Social Support from rand health for social support, DMSES (Diabetes Management Self Efficacy Scale) for self efficacy and BDI (Beck Depression Inventory)  for depression levels. The sample of this research are 40 responden  for each member  the Diabetes community and Non Member of Diabetes Community with home visit.  The Results of this research show that in Members and Non members of Diabetes Community  have the same characteristics is most : is long suffering DM 1-5 years, Female,not work, no school, low income <UMK, married/ have a partner, routine blood sugar control,  a high level of social support. However, there are differences in outcomes between Diabetes Community Members and Non Diabetes Community Members, age, blood sugar levels, complications,self-care,depression levels, level of self efficacy and quality of life. Quality of Life in Members of the diabetes community at most with a good quality of life 70%  while Non Members of the diabetes community most with poor quality of life 52,5%. It is expected that all diabetics follow the diabetes community because it can improve the quality of life and can improve the management of DM activities for the better.